Biotreatment of As-containing simulated acid mine drainage using laboratory scale sulfate reducing upflow anaerobic sludge blanket reactor. (1st May 2015) - Sahinkaya, Erkan; Yurtsever, Adem; Toker, Yasemin; Elcik, Harun; Cakmaci, Mehmet; Kaksonen, Anna H.
Highlights: As-containing acid mine drainage (AMD) contaminates surface and ground waters. Sulfate reducing bioreactors are viable for treating As-bearing AMD. Granular biomass achieved 4 g/(L d) sulfate reduction from AMD with 10 mg/L As. As removal was low at low heavy metal loads and high H2 S concentrations. The presence of heavy metals and low H2 S concentration improved As removal. Abstract: Heavy metal contamination of water sources can occur from the discharge of acid mine drainage (AMD). This study assessed sulfidogenic treatment of As-, Fe-, Zn-, Ni- and Cu-containing AMD in an upflow anaerobic sludge blanket (UASB) reactor, operated for approximately 500 days. Sulfate reducing granules were successfully enriched with synthetic wastewater and sulfate concentration decreased from 2000 mg/L in the influent to 100–200 mg/L in the effluent. The pH increased from 3–4 to 6–8 as a result of biogenic alkalinity production. Arsenic removal was not detected in the absence of heavy metals, possibly due to the high dissolved sulfide concentration. In the presence of heavy metals, and at low dissolved sulfide concentrations, As removal efficiency increased to 98–100% likely due to the formation of arsenopyrite (FeAsS) or the adsorption of As on metal sulfide precipitates. Fe, Cu, Ni and Zn removal efficiencies approached 99% in the presence of dissolved sulfide. When hydrogen sulfide generation was insufficient to precipitate all of the metals, Fe was detected in the UASB effluent. The results showed that As-, Fe-, Zn-, Ni- and Cu-containing AMD can be effectively treated by sulfate reducing granules in UASB reactors.